Pelatihan Pembuatan Brosur dan Video Promosi Berbahasa Inggris di Kamwis - Ermerawati, Anesti Budi; Claudia, Sarah; Damaryanan, Rama E.; Indarto, Christina Helen; Pramesi, Winta Hayu (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2023)
Providing tourism promotion for global tourists needs high concerns of the choice of attractive English vocabulary items and English expressions. To present the village profile along with its distinctive features, the tourist village needs to mesmerize the future global tourists by presenting chosen parts in the brochure. Furthermore, the use of Instagram Reels video becomes a means of promotions that can meet the prospective global visitors more flexibly, attractively, and extensively. The community service program is dedicated for empowering the participants to apply suitable both vocabulary items and English expressions in promoting their tourism villages in many platforms, such as social media and inviting brochure. Through as many as six sessions, the facilitators are hoping that the participants are motivated in applying some promotive English language features when they are both creating promotion brochure and video.